2023
DOI: 10.1364/oe.483452
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tuned active metasurface towards metasurface-integrated liquid crystal on silicon (meta-LCoS) devices

Abstract: Active metasurfaces add a new dimension to static metasurfaces by introducing tunability, and this has received enormous attention from industry. Although various mechanisms have been proposed over the past few years in literature, solutions with good practicality are limited. Liquid crystal (LC)-based active metasurface is one of the most promising approaches due to the well-established LC industry. In this paper, an electrically tunable active metasurface was proposed and experimentally demonstrated using ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Moreover, reconfigurable metasurface is also progressing rapidly towards commercialization [4]. Several mechanisms have been proposed, including immersing metasurface in liquid crystal (LC) environment [5], [6], embedding metasurface on mechanically movable platforms [7], creating metasurface with phasechanging material (PCM) [8], transparent conducting oxide (TCO) [9], nonlinear material [10], and chemically active material [11]. Although these mechanisms may offer unique advantages in terms of response time, endurance, and efficiency, it is challenging to meet the stringent requirements for commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reconfigurable metasurface is also progressing rapidly towards commercialization [4]. Several mechanisms have been proposed, including immersing metasurface in liquid crystal (LC) environment [5], [6], embedding metasurface on mechanically movable platforms [7], creating metasurface with phasechanging material (PCM) [8], transparent conducting oxide (TCO) [9], nonlinear material [10], and chemically active material [11]. Although these mechanisms may offer unique advantages in terms of response time, endurance, and efficiency, it is challenging to meet the stringent requirements for commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limited functionality of passive devices, there have also been attempts on the active tunning of the metasurfaces. [ 24–26 ] Han et al. [ 27 ] utilized electrically tunable graphene metasurfaces to achieve complex amplitude modulation in the 5 µm band.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limited functionality of passive devices, there have also been attempts on the active tunning of the metasurfaces. [24][25][26] Han et al [27] utilized electrically tunable graphene metasurfaces to achieve complex amplitude modulation in the 5 μm band. Kim et al [28] confirmed that the electronically tunable perfect absorption in graphene can be achieved by graphene plasmonic nanostructures, with experimental results demonstrating a tunable wavelength range of 5-8 μm and a switch ratio of ≈96%.…”
Section: Introductionmentioning
confidence: 99%
“…NLCs are anisotropic materials that show large optical birefringence and have been widely used to manipulate light propagation through external stimuli (e.g., electric/magnetic fields, temperature variations, optical fields, etc.). Recent studies have reported on realizing in NLC-based metasurfaces fast-switching photonic devices at optical communication wavelengths, beam-steerable antennas, tunable metalenses, polarization control elements, high-resolution displays, and sensing applications. ,,,, For instance, Sharma and co-workers realized an electrically switchable plasmonic metasurface activated by an NLC layer. The authors observed electrically tunable SLR modes in the near-infrared (NIR) range .…”
Section: Introductionmentioning
confidence: 99%